Employing information security awareness to minimize over-exposure of average Internet user on social networks - Binden, Worawit; Jormae, Maheedeen; Zain, Zakaria; Ibrahim, Jamaludin (IJSRP.ORG, 2014)
Use of Online Social Networking Sites (OSNs) has become ubiquitous nowadays. In the era of a million user social networking sites throughout the world, it becomes increasingly difficult for people to control what they are exposing to whom. In this paper we analyze the influence of social media interactivity features on the exposure of personal data of average Internet user and present techniques to implement information security awareness to minimize over-exposure on OSNs.